Light-Stress Influences the Composition of the Murine Gut Microbiome, Memory Function, and Plasma Metabolome - Kim, Young-Mo; Snijders, Antoine M.; Brislawn, Colin J.; Stratton, Kelly G.; Zink, Erika M.; Fansler, Sarah J.; Metz, Thomas O.; Mao, Jian-Hua; Jansson, Janet K. (Frontiers in Molecular Biosciences, 2019)
The gut microbiome plays an important role in the mammalian host and when in proper balance helps protect health and prevent disease. Host environmental stress and its influence on the gut microbiome, health and disease is an emerging area of research. Exposures to unnatural light cycles are becoming increasingly common due to travel and shift work. However, much remains unknown about how these changes influence the microbiome and host health. This information is needed to understand and predict the relationship between the microbiome and host response to altered sleep cycles. In the present study, we exposed three cohorts of mice to different light cycle regimens for 12 consecutive weeks; including continuous light, continuous dark and a standard light dark regimen consisting of 12 hours light followed by 12 hours of dark. After exposure, motor and memory behavior, and the composition of the fecal microbiome and plasma metabolome were measured. Memory potential was significantly reduced in mice exposed to continuous light, whereas rotarod performance was minimally affected. The overall structure of the microbiome was relatively constant over time. However, Bacteroidales Rikenellaceae was relatively more abundant in mice exposed to continuous dark, while Bacteroidales S24-7 was relatively more abundant in mice exposed to continuous light. The plasma metabolome after the continuous dark exposure differed from the other exposure conditions. Several plasma metabolites, including glycolic acid, tryptophan, pyruvate and several unidentified metabolites, were correlated to continuous dark and light exposure conditions. Specific metabolites including erythritol, serotonin, and ribitol were correlated to the abundances of the microorganism Bacteroidales S24-7 based on light exposure. This study provides the foundation for future studies into the mechanisms underlying the role of the gut microbiome on the murine host during light-dark stress.